Body Composition Parameters, Adiponectin, Leptin and Adiponectin/Leptin Ratio are Correlated with LH/FSH Ratio in Women with PCOS but not in Women without PCOS - Gita Pratama; Wiweko, Budi; Asmarinah; Widyahening, Indah Suci; Andraini, Trinovita; Hartanto Bayuaji; Andon Hestiantoro (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objective: To investigate the correlation between body composition parameters, adiponectin, leptin and the adiponectin/leptin ratio and the LH/FSH ratio in women with polycystic ovary syndrome (PCOS). Methods: A cross-sectional study was conducted at Reproductive Cluster Yasmin, Dr. Cipto Mangunkusumo General Hospital, Jakarta, Indonesia, with sixty women with PCOS and sixty healthy women as controls (matched for age and BMI). Body composition parameters, including body weight, body mass index (BMI), waist circumference (WC), waist to hip ratio (WHR), percent body fat (PBF), visceral fat area (VFA), percent subcutaneous fat (PSF) and skeletal muscle mass (SMM), were measured; levels of fasting glucose, fasting insulin, testosterone, and sex hormone binding globulin (SHBG) were measured; and homeostatic model assessment for insulin resistance (HOMA-IR) values, anti-Mullerian hormone (AMH), free androgen index (FAI), Ferriman-Gallwey (FG) score, adiponectin levels, leptin levels, adiponectin/leptin ratio, LH, FSH and LH/FSH ratio were measured. Results: Body composition parameters (body weight, BMI, WC, WHR, PBF, VFA, PSF, SMM) were not significantly different between women with PCOS and controls. Fasting insulin (P<0.05), HOMA-IR (P<0.05), AMH (P<0.01), FAI (P<0.01), FG score (P<0.01) and LH/FSH ratio (P<0.05) were higher in PCOS women. Adiponectin (P<0.01) was lower in PCOS women, while leptin and the adiponectin/leptin ratio were not significantly different between groups. Most of body composition parameters, adiponectin, leptin and adiponectin/leptin ratio were correlated with HOMA-IR in both groups. SMM was positively correlated with the LH/FSH ratio, while body weight, BMI, WC, PBF, VFA, and PSF were inversely correlated with the LH/FSH ratio in PCOS patients but not in controls. WHR was not correlated in either group. Leptin (r=-0.278; P<0.05) was negatively correlated with the LH/FSH ratio only in the PCOS group. Adiponectin (r=0.394; P<0.01) and the adiponectin/leptin ratio (r=0.413; P<0.01) were also positively correlated with the LH/FSH ratio only in the PCOS group. AMH was correlated with the LH/FSH ratio, whereas testosterone level, FAI, FG score, fasting insulin level and HOMA-IR value were not correlated with the LH/FSH ratio in PCOS women. Conclusion: Most of the body composition parameters, leptin, adiponectin and the adiponectin/leptin ratio were significantly correlated with HOMA-IR in both groups. However, correlations of those parameters with LH/FSH ratio were found only in PCOS but not in women without PCOS. Adiponectin and leptin may play a significant role in the mechanism of neuroendocrine disorders in PCOS, which is characterized by an increased LH/FSH ratio. Keywords: adiponectin, adiponectin/leptin ratio, body composition, HOMA-IR, leptin, LH/FSH ratio, PCOS